Protection and Defence of Railway Transport against International Terrorism - Lubomir Ciganik; Iveta Balasicova (Communications - Scientific letters of the University of Zilina, 2008)
The authors deal with the threat of international terrorism for the EU and global community and target the attention to infrastructure, critical infrastructure and rail transport. They analyse the EU approach towards the protection of critical infrastructure and point out the core criteria and principles of processing the protective system in separate countries. Moreover they concentrate on the protection of rail transport and possibilities of terrorist attacks. The last part presents danger of radiological terrorism and danger related to transport of radiological material on rails.